Political Monopoly: A Study of the Progressive Conservative Association in Rural Alberta 1971-1996 - Neitsch, Alfred Thomas (Université d'Ottawa / University of Ottawa, 2011)
This dissertation argues that the Alberta Progressive Conservative organization constructed a rural political monopoly that facilitated a general provincial political monopoly. It will argue that rural Alberta was vital for the rise of the Progressive Conservatives and accounted for much of its success over the subsequent twenty-five years. The argument also challenges the theories of ‘responsible party government’ that have traditionally explained the perpetuation of the quasi-party system and tradition of one-party dominance in Alberta. It argues that a more comparative approach, specifically the thesis of democratic quality, be integrated into this field of study. The employment of democratic quality biases and the consolidation of economic power in rural Alberta contributed heavily to Conservative political success between 1971 and 1996. Over this period, the Conservatives perpetuated a system of electoral malapportionment that overrepresented rural constituencies and underrepresented urban ridings. At the same time the Conservatives actively challenged independent rural/agrarian civil society organizations and any policy contrary to the party’s political interests. Alberta’s once considerable independent rural and agrarian lobby is today predominantly mediated by their position within or in relation to the Progressive Conservative Association. The decline of general farm organizations (GFOs) and agrarian civil society organizations, facilitated in part by government complicity and a changing agricultural economy, resulted in a ‘political monopoly’ in rural areas. During this period malapportionment underpinned a general political monopoly with rural overrepresentation shoring up collapses of urban support (i.e. Edmonton) in the 1980s and 1990s. This work will provide evidence of participation, competition and other democratic quality biases through a construction of this theoretical framework in terms of a broader comparative perspective based on the evaluation of ‘democratic quality’.
Keywords: Alberta Politics; Canadian Politics; Comparative Politics